Tectonic structure and evolution of the upper plate of Vlahokerasia Metaporphic core (Central Peloponnesus) - ΣΚΟΥΡΤΣΟΣ, Ε.; ΑΛΕΞΟΠΟΥΛΟΣ, Α.; ΛΕΚΚΑΣ, Σ. (Bulletin of the Geological Society of Greece, 2001)
The geological structure of Vlahokerasia metamorphic core is consisted by a series of imbricated tectonic units, the occurrence of which, from the bottom to the top is as follows: Marbles, Phylites-Quartzites, Tripolitza and Pindos unit. Nevertheless, it has often been observed that some units are juxtaposed, not on the immediate tectonically underlying unit but on even lower units (i.e. Pindos unit lies directly on the Phyllites-Quartzites unit). The first two units, which have undergone Late Oligocene - Early Miocene HP/LT metamorphism, represents the lower plate of the metamorphic core, whereas the latter two (Pindos and Tripolitza units) correspond to the upper plate. The rocks of the upper plate are mainly characterized by a relatively small thickness (<300m) and they are strongly tectonized by two sets of normal faults. The main fault system trends in a ΝW orientation whereas the second one, which is younger, intersects the first set in a NNE orientation. Fault plane solutions performed on the previous-mentioned fault scarps showed a NE-SW oriented extensional stress distribution. In order to study the extensional tectonics, which has obviously influenced the fabric of the whole upper plate, a cross-section parallel to the main extensional axis and very close to the detachment surface has been constructed. The restoration of the cross-section showed that the extension of the upper plate was a result of the function of two sets of 'domino faults' of, relatively, opposite polarity. The gradual activation of these two sets of faults caused a severe thinning of the upper plate, expressed by a horizontal extensional deformation in the order of 302-422 %. Based on the existing radiochronological data, derived from the lower plate and on the age of the postalpine formations, which cover uncomformably the older structures, we assume that the extensional deformation of the upper plate took place during Early Miocene-Lower Pliocene. Regarding the post-alpine sediments, they have been deposited into basins created during the activity of a NW-oriented normal fault system, which cut through the older extensional features.